Cover Picture: Direct Fluoro‐aminosulfenylation of Active Methylenes by Dialkylaminosulfur Trifluorides under Catalyst‐Free Conditions (Asian J. Org. Chem. 10/2016). Issue 10 (4th October 2016) - Saidalimu, Ibrayim; Guo, Ming; Tokunaga, Etsuko; Shibata, Norio
Abstract : The direct fluoro‐aminosulfenylation reaction of active methylene compounds using diethylaminosulfur trifluoride (DAST) affords α‐fluoro‐α‐aminosulfenyl compounds with a tetrasubstituted carbon center in high yields. DAST is a well‐known reagent for the nucleophilic fluorination of carbonyls since 1975, and now it can be used for the fluoro‐aminosulfenylation of methylenes, which is a more atom‐economical reaction. The background picture is intended to explain the new use of part of my old house, which was used as a bath since 1965 and is still being used by others for different purposes. More information can be found in the Communication by Norio Shibata et al. onpage 1208 in Issue 10, 2016 (DOI:10.1002/ajoc.201600264 ).